Literacy Pedagogies of a Reception Class in England: An Ethnographic Case Study - Firat, Kubra (2021)
In recent years England’s education system has experienced interventionist, neo-liberal educational reforms focused on the everyday literacy pedagogies of early years teaching staff. These reforms, which have included high-stakes accountability measures, have given rise to contentious political debates regarding their impact on values and practice in primary schools. This study focuses on exploring these debated practices through an in-depth exploration of the literacy pedagogies in one reception class within a maintained primary school in order to answer the research question: ‘what matters in shaping literacy pedagogies in a reception class in England?’.